2018
DOI: 10.1007/s12192-017-0860-3
|View full text |Cite
|
Sign up to set email alerts
|

Yeast polyubiquitin gene UBI4 deficiency leads to early induction of apoptosis and shortened replicative lifespan

Abstract: Ubiquitin is a 76-amino acid protein that is highly conserved among higher and lower eukaryotes. The polyubiquitin gene UBI4 encodes a unique precursor protein that contains five ubiquitin repeats organized in a head-to-tail arrangement. Although the involvement of the yeast polyubiquitin gene UBI4 in the stress response was reported long ago, there are no reports regarding the underlying mechanism of this involvement. In this study, we used UBI4-deletion and UBI4-overexpressing yeast strains as models to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…A Ub molecule can be fused to the C‐terminal ribosomal proteins (r‐proteins) Rpl40A/B of Ubi1/2 and the C‐terminal protein Rps31 of Ubi3 or self‐fused to form a pentamer of Ubi4 (Ozkaynak et al ., ; Finley et al ., ). Ubi4 is a polyUb precursor consisting of variable Ub repeats organized in a head‐to‐tail manner (Zhao et al ., ), and the numbers of the repeats are crucial for cellular proteostasis and stress response (Gemayel et al ., ). The diversity of the Ub signalling stems from a Ub ability to form polyUb chains through covalent linkage between the εNH 2 group of a specific Lys (K6, K11, K27, K29, K33, K48 or K63) or the αNH 2 group of the first Met residue (M1) on one Ub molecule and the C‐terminus of another Ub molecule (Castaneda et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Ub molecule can be fused to the C‐terminal ribosomal proteins (r‐proteins) Rpl40A/B of Ubi1/2 and the C‐terminal protein Rps31 of Ubi3 or self‐fused to form a pentamer of Ubi4 (Ozkaynak et al ., ; Finley et al ., ). Ubi4 is a polyUb precursor consisting of variable Ub repeats organized in a head‐to‐tail manner (Zhao et al ., ), and the numbers of the repeats are crucial for cellular proteostasis and stress response (Gemayel et al ., ). The diversity of the Ub signalling stems from a Ub ability to form polyUb chains through covalent linkage between the εNH 2 group of a specific Lys (K6, K11, K27, K29, K33, K48 or K63) or the αNH 2 group of the first Met residue (M1) on one Ub molecule and the C‐terminus of another Ub molecule (Castaneda et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The function of Ubi4 has been well explored in various yeasts. Deletion of ubi4 in S. cerevisiae may result in increased sensitivity to oxidative stress, apoptotic phenotype and shortened lifespan (Zhao et al ., ) as well as induced H 2 S production (Yoshida et al ., ). Ubi4 is important for an integrity of spindle pole bodies at meiotic stage of fission yeast (Okazaki et al ., ) and essential for stress tolerance and improved fermentation during ethanol production of wine yeast (Wu et al ., ; Peter et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the monomeric ubiquitin fusion gene only encodes a single ubiquitin repeat that is finally fused to unrelated peptide sequences [8]. Previous research in Saccharomyces cerevisiae suggested that the polyubiquitin gene ( UBI4 ) encoded 5 tandem ubiquitin repeats and was highly induced under stress conditions, whereas the monomeric ubiquitin fusion genes were the primary contributors to cellular ubiquitin synthesis under normal conditions [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, polyubiquitin gene expression at the transcription level was observed to be significantly upregulated under environmental stress in different pathogenic fungi [13,14,15]. Subsequently, many polyubiquitin genes have been functionally characterized via gene deletion in several fungi including S. cerevisiae [6,11,16]; the human pathogen, Candida albicans [17]; and the plant pathogenic fungi, Magnaporthe oryzae and Cryphonectria parasitica [12,18]. For example, deletion of the yeast polyubiquitin gene UBI4 resulted in reduced resistance to stresses such as high temperature and oxidative stress [6,11,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation